Food Environment index is inversely associated with cancer survival in North Carolina - Shenghui Wu; Sarah Ulrich; Tinghao Feng; Yanning Liu; Leilani Tseng (PLoS ONE, 2025)
Background Exploring the potential role of the food environment on cancer survival could inform prevention and control strategies to improve cancer survivorship. This study examined the associations between the food environment index (FEI) and survival for overall cancer in North Carolina. Methods This retrospective cohort study included 1,292,991 patients diagnosed with overall cancer from January 1, 2000, to December 31, 2022, from the North Carolina Cancer Central Registry. Individual-level demographic, tumor, and treatment data were provided by the North Carolina Cancer Central Registry. FEI and other county-level exposures were obtained from the County Health Rankings & Roadmaps databases. The county-level food environment index measures access to healthy foods (0 is worst, 10 is best). Cox regression was used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) for the associations between FEI and cancer survival, adjusting for individual-level and county-level covariates. Results Higher levels of FEI were associated with statistically significant better survival for overall cancer. The fully adjusted HR for every unit increase in FEI score was 0.983 (95% CI: 0.979, 0.988; P < 0.0001). The adjusted HR for the 3rd quartile vs. 1st quartile was 0.98 (95% CI: 0.94, 0.99), and for the 4th quartile vs. 1st quartile it was 0.95 (95% CI: 0.94, 0.96). Conclusion These results suggest that a healthy food environment, as measured by FEI, may be a protective factor for cancer survival in North Carolina. To improve cancer survival, further strategies to enhance the food environment at the county level are warranted.